An impact of inflation on the neo-Keynesian Phillips curve - the case of The Republic of Serbia - Vukadinović, Simonida D; Andrejević Panić, Andrea (Poslovna ekonomija, 2024)
Phillips curve has become systematic instrumentation that elaborates macroeconomic analysis showing relations between unemployment and inflation, illustrating the trade-off between achieving full capacity engagement and maintaining price stability. The New Keynesian Phillips curve presumes that expectations of inflation are not adaptive and rational, as withheld from Lucas’s theory. ANew Keynesian Phillips curve was there as a result has emerged which is distinctive from the curve modeled by Phelps and Friedman In 2023 counting a peak of 16.2% in March, inflation rate gently declined to 10.2% in September, and helped by reducing pressure from food prices. Projected inflation is to decelerate further till the end of 2023 and in next year, based on effects and tighter financing conditions. Although some increase in 2023 is evident, approximate yearly inflation is expected to be single digits in 2024, returning within the central bank’s target in two years. This paper will present The New Keynesian Phillips curve in the Republic of Serbia (Serbia), as well as macroeconomics predictions in the country.